2005
DOI: 10.1016/j.jmb.2005.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Site-saturation Mutagenesis is more Efficient than DNA Shuffling for the Directed Evolution of β-Fucosidase from β-Galactosidase

Abstract: Protein engineers use a variety of mutagenic strategies to adapt enzymes to novel substrates. Directed evolution techniques (random mutagenesis and high-throughput screening) offer a systematic approach to the management of protein complexity. This sub-discipline was galvanized by the invention of DNA shuffling, a procedure that randomly recombines point mutations in vitro. In one influential study, Escherichia coli β-galactosidase (BGAL) variants with enhanced β-fucosidase activity (tenfold increase in k cat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 39 publications
0
39
0
1
Order By: Relevance
“…Nevertheless, it does not belong to GH1 or GH30, which have ␤-Fuc activity (the CAZy database). It has been reported that E. coli LacZ, which has a GH2 domain, recognizes and catalyzes a reaction with ␤-D-fucosyl moieties weakly (31,32). We showed that truncated MsgA containing only LacZD demonstrated ␤-Fuc activity (Table 4).…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, it does not belong to GH1 or GH30, which have ␤-Fuc activity (the CAZy database). It has been reported that E. coli LacZ, which has a GH2 domain, recognizes and catalyzes a reaction with ␤-D-fucosyl moieties weakly (31,32). We showed that truncated MsgA containing only LacZD demonstrated ␤-Fuc activity (Table 4).…”
Section: Discussionmentioning
confidence: 60%
“…However, mutations closer to the catalytic core appear to have a greater effect on the selected catalytic activity (30)(31)(32)(33). These residues for mutagenesis may be selected through a random, rational or combined evolutionary approach.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of saturation mutagenesis (16)(17)(18) for effective diversity generation coupled with highly efficient recombination tools and the use of statistical analysis to maximize screening efficiency was used to improve DvCA. In nine rounds of evolution, over 27,000 DvCA variants were screened at increasingly higher temperatures in the presence of 3.0-4.2 M MDEA to identify enzymes with the desired characteristics.…”
Section: Significancementioning
confidence: 99%